The effect of a multi-ingredient pre-workout supplement on time to fatigue in NCAA Division I cross-country athletes - Fye, H.; Pass, C.; Dickman, K.; Bredahl, E.; Eckerson, J.; Siedlik, J. (Nutrients, 2021)
This investigation aimed to determine the effect of a multi-ingredient pre-workout supplement (MIPS) on heart rate (HR), perceived exertion (RPE), lactate concentration, and time to fatigue (TTF) during a running task to volitional exhaustion. Eleven NCAA Division I cross-country runners (20 ± 2 year; height: 171 ± 14 cm; weight: 63.5 ± 9.1 kg) participated in this randomized, double-blind, placebo-controlled cross-over study. Bayesian statistical methods were utilized, and parameter estimates were interpreted as statistically significant if the 95% highest-density intervals (HDIs) did not include zero. TTF was increased in the MIPS condition with a posterior Meandiff = 154 ± 4.2 s (95% HDI: -167, 465) and a 0.84 posterior probability that the supplement would increase TTF relative to PL. Blood lactate concentration immediately post-exercise was also higher in the MIPS condition compared to PL with an estimated posterior Meandiff = 3.99 ± 2.1 mmol (95% HDI: -0.16, 7.68). There were no differences in HR or RPE between trials. These findings suggest that a MIPS ingested prior to sustained running at lactate threshold has an 84% chance of increasing TTF in highly trained runners and may allow athletes to handle a higher level of circulating lactate before reaching exhaustion.